Cost efficiency versus disruption: Are traditional universities doomed? - Serfontein, C. (South African Journal of Higher Education, 2025)
Internationally, universities face the consequences of the disruption caused by the Fourth Industrial Revolution, accelerated by COVID–19. Traditional universities have lost their competitive advantage due to rapidly changing skills needed and online learning gaining momentum. Historically, universities benefitted from higher levels of enrolments, also increasing their tuition fees above inflation with researchers indicating their concern, but failing to address the reason(s) for this increase. To assess the extent to which universities are geared to face the disruption of potentially declining enrolments with limited opportunity to increase tuition fees in the future (relevance of skills, more competition, students having more choices), it is imperative to assess why tuition fees increased above inflation in the past. The focus of this quantitative research study is to establish the level of efficiency of managing Expenses amongst a sample of sixteen publicly funded South African universities from 2010 to 2019. The data was secondary data in the public domain. Serious levels of financial distress caused by declining enrolments have already been reported in many universities in the United Kingdom (UK), Europe, the United States of America (USA) and Australia. The research question addressed in this article is to assess what the reasons are for the abnormal increases in tuition fees in the past with the intent to assist universities in the future if (when) the disruption of declining enrolments and lower tuition fees is realised. Although this study focused only on South African universities, the unique contribution of this research is the methodology applied using Management and Cost accounting to assess the efficient management of expenses at South African universities from 2010 to 2019.